Hope in difficult times - Editorial Board of "Biophysical Bulletin" (Biophysical Bulletin, 2022)
Editorial board of the “Biophysical bulletin” scientific journal in this difficult time, together with all Ukrainian people, is continuing to work to restore the peaceful life in Ukraine as soon as possible.